Regulation of Plant Tannin Synthesis in Crop Species - Mora, José; Pott, Delphine M.; Osorio, Sonia; Vallarino, José G. (Frontiers in Genetics, 2022)
Plant tannins belongs to plant antioxidant compounds family, which are chemicals responsible of protecting biological structures from the harmful effect of oxidative stress. A wide broad of plants and crops are rich in antioxidant compounds, offering plant resistance to biotic, mainly pathogens and herbivores attacks, and abiotic stresses, such light and wound stresses, but also are related to human health benefits and protective effects in cardiovascular and neurodegenerative diseases, despite provide anti-tumor, anti-inflammatory and anti-bacterial characteristics. Most of these compounds are structurally and biosynthetically related through the shikimate-phenylpropanoid pathway, offering several classes of plant antioxidants: flavonoids, anthocyanins and tannins. Tannins are divided into two major classes: condensed tannins or proanthocyanidins and hydrolysable tannins. Hydrolysable tannins derived directly from a shikimate pathway intermediary but condensed tannins are derived from flavonoids pathway, one of the branches of the shikimate pathway. Both type of tannins has been proposed as important molecules for taste perception of many fruits and beverages, especially wine, despite well-known role in plant defense and human health. Regulation at gene level, biosynthesis and degradation have been studied in condensed tannins extensively in plants species like grapevine (Vitis vinifera), persimmon (Diospyros kaki) and several berries species. On the other hand, the available information of hydrolyzable tannins is much lesser, but several aspects regarding their biosynthesis and regulations haven been recently discovered